Integrated analysis of potential microbial consortia, soil nutritional status, and agro-climatic datasets to modulate P nutrient uptake and yield effectiveness of wheat under climate change resilience - Yahya, Mahreen; Rasul, Maria; Hussain, Sayed Zajif; Dilawar, Adil; Ullah, Midrar; Rajput, Lubna; Afzal, Aftab; Asif, Muhammad; Wubet, Tesfaye; Yasmin, Sumera (Frontiers in Plant Science, 2023)
Climate change has a devastating effect on wheat production; therefore, crop production might decline by 2030. Phosphorus (P) nutrient deficiency is another main limiting factor of reduced yield. Hence, there is a dire need to judiciously consider wheat yield, so that human requirements and nutrition balance can be sustained efficiently. Despite the great significance of biostimulants in sustainable agriculture, there is still a lack of integrated technology encompassing the successful competitiveness of inoculated phosphate-solubilizing bacteria (PSB) in agricultural systems in the context of climatic conditions/meteorological factors and soil nutritional status. Therefore, the present study reveals the modulation of an integrated P nutrient management approach to develop potential PSB consortia for recommended wheat varieties by considering the respective soil health and agro-climatic conditions. The designed consortia were found to maintain adequate viability for up to 9 months, verified through field emission scanning electron microscopy and viable count. Furthermore, a significant increase in grain yield (5%–8%) and seed P (4%) content was observed in consortia-inoculated wheat plants with 20% reduced Diammonium phosphate (DAP) application under net house conditions. Fluorescence in situ hybridization analysis of roots and amplification of the gcd gene of Ochrobactrum sp. SSR indicated the survival and rhizosphere competency of the inoculated PSB. Categorical principal component analysis (CAT-PCA) showed a positive correlation of inoculated field-grown wheat varieties in native soils to grain yield, soil P content, and precipitation for sites belonging to irrigated plains and seed P content, soil organic matter, and number of tillers for sites belonging to Northern dry mountains. However, the impact of inoculation at sites belonging to the Indus delta was found significantly correlated to soil potassium (K) content, electrical conductivity (EC), and temperature. Additionally, a significant increase in grain yield (15%) and seed P (14%) content was observed in inoculated wheat plants. Thus, the present study demonstrates for the first time the need to integrate soil biological health and agro-climatic conditions for consistent performance of augmented PSB and enhanced P nutrient uptake to curtail soil pollution caused by the extensive use of agrochemicals. This study provides innovative insights and identifies key questions for future research on PSB to promote its successful implementation in agriculture.